The Role of Each Family Support for Living Cost Balance A Structural-Functional-Normative Analysis Approach - Yazid, Afthon (Institut Agama Islam Negeri Metro, 2023)
This study discusses the crucial role of the person responsible for family support in maintaining economic balance in the family structure. Through a Structural-Functional-Normative analysis approach, this study explores the dynamics of interactions that shape the role of the person in charge of income as a central element in maintaining the balance of family economic functioning. The focus of research includes normative aspects that influence this role and its impact on family economic stability. By integrating structural, functional, and normative dimensions, this study aims to provide insight into how the role of the person in charge of providing for the role of the income person plays a role in maintaining family economic balance. The results of the study show that family support in the family maintains a fixed financial balance taken by the role of a husband as a household. The failure of the husband in financial maintenance can have a structurally functional impact on the position of a family.